Pengaruh Jenis Kelamin, Usia, dan Religiusitas terhadap Kesehatan Mental Remaja - Afriani, Afriani; Lestari, Nuzul Mela (PHILANTHROPY: Journal of Psychology, 2017)
Mental health becomes an major issue and has been of growing concern recently, but only few empirical studies focused on adolescence?s mental health especially in Aceh.  The current study aimed to determine the effect of sex, age, and religiosity on mental health among adolescents in Banda Aceh. A total of 342 students from four high school students in Banda Aceh was selected using Multi-Stage Cluster and Non-Proportionate Stratified Random Sampling. Mental health and religiosity were measured using Mental Health Inventory adapted from Veit and Ware, and Religiosity Scale developed by researchers from Muslim religiosity theory by Hamzah et al., respectively.  Data was analyzed using multiple regression analysis. Result of the study found that religiosity was significantly contributed to adolescents? mental health (?=0,29, p<0.01), indicated that higher score on religiosity scale was followed by higher score on mental health. Meanwhile, sex (?=-0,04, p>0,05) and age (?=0,04, p>0,05)  did not predict mental health in the present study. It showed that a sense of connectedness to God and higher level of religious involvement play an important role on adolescents? mental health. Findings of the study give a valuable information  for the development of mental health promotions for adolescents, particularly in Banda Aceh.